Engaging children and adolescents with acquired brain injury and their families in goal setting: The family perspective. Issue 1 (2nd January 2023) - Collins, Alana; D'Cruz, Kate; Jackman, Angie; Anderson, Vicki; Jenkin, Taylor; Scheinberg, Adam; Muscara, Frank; Knight, Sarah
ABSTRACT: This study explored the experiences of goal setting in paediatric rehabilitation from the perspectives of children and adolescents with acquired brain injury (ABI) and their parents in paediatric rehabilitation. Using a qualitative research design, 15 semi-structured interviews were conducted with 13 parents and 8 young people with ABI aged between 9 and 18 years who were engaged in outpatient rehabilitation. Interview transcripts were analysed using constructivist grounded theory methods. Two main themes and several sub-themes emerged: Experiences of goal setting: The role of professionals; The role of the young person; and The role of the parents. Working as a team: Understanding each other and building trust; Communicating, sharing knowledge and different perspectives; and Being flexible. These themes reflect parent's and young people's experience of goal setting during paediatric rehabilitation for ABI and suggest clinicians play an important role in educating young people and their families about goal setting in the outpatient rehabilitation context. Young people and their parents also perceive the focus of outpatient rehabilitation as working collaboratively with clinicians to gain knowledge to manage the consequences of ABI. Our findings emphasize the importance of the therapeutic consumer–clinician relationship and the need to actively engage young people in goal setting.